Application of Unmanned Aerial Vehicle (UAV)-Acquired Topography for Quantifying Typhoon-Driven Landslide Volume and Its Potential Topographic Impact on Rivers in Mountainous Catchments - Kuo-Jen Chang; Chun-Wei Tseng; Chih-Ming Tseng; Ta-Chun Liao; Ci-Jian Yang (Applied Sciences, 2020)
Landslides are highly erosional processes that dominate sediment mobilization and reshape landscapes in orogenic belts. Therefore, quantifying and characterizing landslide volume is essential to disaster prevention and understanding landscape evolution in mountainous rivers. Progressive development of the structure-from-motion (SfM) and multi-view stereo (MVS) photogrammetric techniques and Unmanned Aerial Vehicles (UAV) provides low-cost and high-resolution digital elevation models (DEMs), compared to traditional aerial photogrammetry at the same resolution. In this study, we quantified landslide volume and change in river channel volume at meter-scale accuracy for the Laishe River catchment of southern Taiwan from 2009 to 2015, which provides reliable data for discussing sediment transport and morphological response. The observations indicate that Typhoon Morakot in August 2009, induced a landslide volume of 31.63 million (M) m3, which is equal to 87% of the six-year sediment production. Typhoon Morakot also caused the deposition of 8.2 M m3 in the Laishe River. Additionally, this study demonstrates the feasibility of using UAVs to quantify the migration of landslide material and changes in channel area and volume, and the detection of landslide dams. In conclusion, two sources of images, especially those by UAVs, were used to decipher the consequence and potential hazard, social impact, and morphological changes in a mountainous river.